DIFFUSION OF INNOVATIONS: AN ASSESSMENT OF BUILDING INFORMATION MODELLING UPTAKE TRENDS IN SOUTH AFRICA - Tim FROISE; Winston SHAKANTU (Journal of Construction Project Management and Innovation)
Building information modelling (BIM) is currently being adopted by the South African industry, although current uptake is lagging behind other countries. The construction industry internationally is realising the benefits of using a single source of construction information, and the increasing functionality of the hardware, software and connectivity is providing an environment for the different organisations involved with a construction project to collaborate. The study evaluates adoption in South Africa and other countries using the line of enquiry known as the ‘diffusion of innovations’ to determine a trend in South Africa and to predict rates of adoption based on those of other countries. Factors that inhibit take-up in South Africa are examined and recommendations are made based on the findings of the research.